THU0204 Real world experience of biosimilar switching at the norfolk & norwich university hospital, united kingdom. (12th June 2018) - Steel, L.; Marshall, T.; Loke, M.
Abstract : Background: Tumour Necrosis Factor (TNF) inhibitors are routinely used in managing rheumatoid arthritis (RA), psoriatic arthritis (PsA) and spondyloarthritis (SpA). In 2012 and 2015, the patents for the Etanercept (ETN) and Infliximab (IFX) originator molecules expired in Europe respectively and the use of biosimilar ETN and IFX was approved for use in England. Objectives: To determine the proportion of rheumatology patients who experienced a flare of their disease following a switch from originator to biosimilar IFX or ETN and in those who flared, to determine whether disease control can be re-captured following reverting to the originator product. Methods: This was a retrospective study of all patients switched from their originator IFX or ETN to their corresponding biosimilar product between July 2016 and July 2017 at a UK tertiary rheumatology centre. A total of 475 patients were identified by our Biologics team. Seventeen patients experienced a flare defined by: an increase in Disease Activity Score (DAS)28>1.2 points in RA, worsening of any of the Psoriatic Arthritis Response Criteria (PsARC) in PsA, an increase in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) of at least 1 unit in SpA, and worsening of swollen and tender joint count in our patient with adulthood juvenile idiopathic arthritis (JIA). Follow-up at 3 months determined disease re-capture, defined by an improvement in DAS28 score >1.2 units, improvement in at least two of the PsARC, one to be tender or swollen joint score, an improvement of BASDAI score and improved swollen and tender joint count in our patient with adulthood JIA. Results: Nine patients (9.2%) who switched to biosimilar IFX flared: four with RA, two with PsA, two with SpA and one with JIA. Of those, three patients (33.3%) were able to re-capture disease control on switching back to originator IFX. Two patients (2.0%) experienced side effects on switching to biosimilar IFX. Eight patients (2.1%) experienced a flare on switching to biosimilar ETN: four with RA, one with PsA and three with SpA. Of those, seven patients (87.5%) re-captured disease control on switching back to originator ETN. Ten patients (2.7%) experienced side effects on switching to biosimilar ETN. Conclusions: The majority of our patients did well following the switch to biosimilar IFX and ETN. Patients who did flare on biosimilar ETN are more likely to re-capture their disease control than those who flared on biosimilar IFX. This adds to real-world evidence to support the European League Against Rheumatism recommendations to utilise biosimilar therapy in rheumatology practice, which is likely to include patients who differ from those enrolled in clinical trials; important when considering health economy implications. Acknowledgements: With thanks to patients and consultant colleagues at the Norfolk and Norwich University Hospital. Disclosure of Interest: None declared